2017
DOI: 10.2139/ssrn.3012120
|View full text |Cite
|
Sign up to set email alerts
|

Media Competition, Information Provision and Political Participation: Evidence from French Local Newspapers and Elections, 1944-2014

Abstract: This paper investigates the impact of increased media competition on the quantity and quality of news provided and, ultimately, on political participation. I build a new county-level panel dataset of local newspaper presence, newspapers' number of journalists, costs and revenues and political turnout in France, from 1944 to 2014. I estimate the effect of newspaper entry by comparing counties that experience entry to similar counties in the same years that do not. Both sets of counties exhibit similar trends pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 80 publications
2
40
0
Order By: Relevance
“…14 We find that the impact on the top two candidates' vote share stays 14 Proxying the level of information by the salience of the race is a strategy also used by Hall and Snyder (2015). Data on local newspaper circulation were collected by Julia Cagé (see Cagé (2017)). We collected the equally high in parliamentary elections and in districts with media exposure higher than the median or the second tercile (Tables F-I, F-IV, and F-V in Appendix F of the Supplemental Material), and that it remains unaffected by the gap between the strength of the third candidate and of each of the top two in these subsamples (Tables F-II and F-VI to F-VIII in Appendix F). A fourth possible interpretation for switchers' behavior that is consistent with instrumental motives is that these voters are not short-term but long-term instrumentally rational (Castanheira (2003)).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…14 We find that the impact on the top two candidates' vote share stays 14 Proxying the level of information by the salience of the race is a strategy also used by Hall and Snyder (2015). Data on local newspaper circulation were collected by Julia Cagé (see Cagé (2017)). We collected the equally high in parliamentary elections and in districts with media exposure higher than the median or the second tercile (Tables F-I, F-IV, and F-V in Appendix F of the Supplemental Material), and that it remains unaffected by the gap between the strength of the third candidate and of each of the top two in these subsamples (Tables F-II and F-VI to F-VIII in Appendix F). A fourth possible interpretation for switchers' behavior that is consistent with instrumental motives is that these voters are not short-term but long-term instrumentally rational (Castanheira (2003)).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…These two findings suggest that-relative to local newspapersnational newspapers reacted to the drop in advertising revenues by producing less journalistic-intensive content. To the extent that the size of the newsroom is a good proxy for news quality (see, e.g., Hamilton 2006;Berry and Waldfogel 2010;Fan 2013;Cagé 2017;Cagé, Hervé, and Viaud 2017), our results highlight a positive relationship between advertising revenues and quality of information. Also, we study the front page content of a subsample of newspapers and find suggestive evidence that national newspapers decreased their provision of hard news following the introduction of television advertising.…”
Section: Newspapers In Times Of Low Advertising Revenues †mentioning
confidence: 66%
“…Effect on "Quality".-Two features of newspapers have been repeatedly used in the literature as measures of newspaper quality (or at least production of journalistic-intensive content): the number of journalists and the so-called newshole (the amount of space in the newspaper devoted to anything but advertising) (see, e.g., Hamilton 2006;Berry and Waldfogel 2010;Fan 2013;Cagé 2017;Cagé, Hervé, and Viaud 2017). 51 Anderson and Waldfogel (2015) for instance note that "(i)n newspapers, some of the direct input cost measures-page length and staff size-are directly suggestive of quality."…”
Section: B Resultsmentioning
confidence: 99%
“…Absent this K (·) term, it is clear that the exposure of fake news can only be welfare‐reducing in this model: not only does debunking use real resources but also, when consumers learn that some of their information is false, their valuations of news fall. But a number of studies, as discussed earlier, have suggested that fake news can be harmful to society through the consequences it can have not only for the fact of participation in civil society (such as voting, as in Cagé, ) but for how that participation occurs (see Barrera Rodriguez et al ., .) Consequently, we suppose that there is some aggregate social loss associated with the general falsity of news that people consume.…”
Section: Comparative Static Resultsmentioning
confidence: 99%
“…This bias can arise in equilibrium, although it makes all market participants worse off. Finally, a recent paper by Cagé () provides an example of a Hotelling model of newspaper markets. She derives results on firm entry and takes them to a data set of French newspapers, that media entry reduces the quantity of ‘hard’ news provision and that this is associated with a decrease in turnout at local elections.…”
Section: Introductionmentioning
confidence: 99%